2001
DOI: 10.1080/09537100120058757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tomato extract on human platelet aggregation in vitro

Abstract: Among all fruits tested in vitro for their anti-platelet property, tomato had the highest activity followed by grapefruit, melon, and strawberry, whereas pear and apple had little or no activity. Tomato extract (20-50 microl of 100% juice) inhibited both ADP- and collagen-induced aggregation by up to 70% but could not inhibit arachidonic acid-induced platelet aggregation and concomitant thromboxane synthesis under similar experimental conditions. The anti-platelet components (MW <1000 Da) in tomatoes are water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…In summary, these results demonstrating the actions of tAF on different platelet functions were all consistent with potential effects mediated partly through polyphenols and PDI and partly through nucleosides elevating cAMP and cGMP levels in platelets [13, 67]. Effects on TF binding suggested that tAF components could have a larger effect on some aspects of the coagulatory response, such as thrombin generation, than previously imagined.…”
Section: In Vitro Studies With Water-soluble Tomato Extract On Human supporting
confidence: 78%
See 4 more Smart Citations
“…In summary, these results demonstrating the actions of tAF on different platelet functions were all consistent with potential effects mediated partly through polyphenols and PDI and partly through nucleosides elevating cAMP and cGMP levels in platelets [13, 67]. Effects on TF binding suggested that tAF components could have a larger effect on some aspects of the coagulatory response, such as thrombin generation, than previously imagined.…”
Section: In Vitro Studies With Water-soluble Tomato Extract On Human supporting
confidence: 78%
“…The antiaggregatory effects of different aqueous fruit extracts on human platelets in vitro have been published previously [13]. The maximum inhibitory effect (70–75 %) was found to be with tomato and kiwi fruit extracts, whereas apple and pear had very little activity (2–5 %).…”
Section: In Vitro Studies With Water-soluble Tomato Extract On Human mentioning
confidence: 87%
See 3 more Smart Citations